Trust Remains the Foundation of my Practice - Saria Gouher (Patient Experience Journal)
Navigating healthcare while managing the complexities of disease, especially in elderly individuals, is challenging for both patients and their families. Physicians play a crucial role as pathfinders in this journey. However, physicians often experience burnout when dealing with patients and families facing complex illnesses. This narrative highlights the characteristics that enable physicians to effectively negotiate with such patients. It describes the experience of an elderly patient during the pandemic, suffering from severe disease complications, and illustrates the uncertainties and fears that families face, feeling as though they are lost in a maze. The physician's role in guiding the patient and family through trust-building is key, achieved through active listening, patience, compassion, availability, and competence. The narrative also emphasizes the importance of a thorough physical examination, which reassures patients that decisions are made after careful evaluation. The first visit of the patient allows the best moment to initially build the trust as patients initially come with recommendation and taking advantage of that initial trust helps to build the trust eventually. Once trust is established, it strengthens the physician-patient relationship, facilitating more straightforward decision-making with families when necessary. This not only reassures patients’ families that the health of their loved ones is valued, but also reduces physician burnout by simplifying the negotiation process.